Design of high sorbent pectin/CaCO3 composites tuned by pectin characteristics and carbonate source. (5th December 2015) - Mihai, Marcela; Steinbach, Christine; Aflori, Magda; Schwarz, Simona
Abstract: Five pectin samples – which differ by the methylation degree and/or amide content – were used to prepare inorganic/organic composites by CaCO3 mineralization from supersaturated solutions. The pectin chemical structure and concentration could control the composite superstructure by induction or orientation of crystal growth. The inorganic materials may also control CaCO3 polymorphism and morphologies and therefore different carbonate sources, such as Na2 CO3, diethylcarbonate or ammonium carbonates, were used as modulators for crystal growth. The morphology of the new CaCO3 /pectin composites was investigated by SEM and the polymorphs content by X-ray diffraction, as compared to bare CaCO3 samples prepared in similar conditions. The composites were tested as sorbents for Cu(II) and Ni(II) ions. Graphical abstract: Highlights: Five pectins which differ by the methylation degree and/or amide content were used. Three carbonate sources (sodium, diethyl and ammonium carbonate) for CaCO3 growth Irrespective of anionic or amide group content in pectin grown almost spherical particles. Polymorph content (vaterite/calcite) is influenced by the preparation conditions. Sorption properties on heavy metal ions depend on the composites polymorph ratio.